2019
DOI: 10.35940/ijeat.a3075.109119
|View full text |Cite
|
Sign up to set email alerts
|

Critical Risk Factors Causing the Time and Cost Overruns of Indian Railway Projects in Indi a

Abstract: Overrun in terms of increase in cost and time of the infrastructure project are considered to be one of India's major infrastructure issues. Any overrun of the infrastructure project will result in huge national losses as it uses taxpayers ' money. These losses can be caused due to poor managent of risk in the construction projects. Overrun is a common phenomenon that affects almost all railway projects. However, the limited effort has been made to limit the occurrence of overruns, the author attempts to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The first stage of synthesizing the 152 literatures is dividing them according to 2 classifications, literatures from the developed countries and literatures from developing countries as presented in Table 2 & 3. (Afzal et al, 2019;Anish et al, 2019;Bhangale, 2016;Chandramohan et al, 2012;Cindrela Devi & Ananthanarayanan, 2017;Ghumare et al, 2019;Kant, 2018;Muthu Venkata Sekar & Mahalakshmi, 2018;Pai et al, 2018;Raju et al, 2017;Shaktawat & Vadhera, 2017;Shanmuganathan & Baskar, 2015;Sharma et al, 2020;Sharma & Goyal, 2019;Shrivastava et al, 2019;Subramani & Sivakumar, 2018;Velumani & Nampoothiri, 2019;Venkateswaran & Murugasan, 2017;Wanjari & Dobariya, 2016) Malaysia 20 (Abdullah et al, 2018;Afzal et al, 2019;Akram et al, 2017;Asmi et al, 2013;Azis et al, 2013;Hameed Memon et al, 2014;Haslinda et al, 2018;Ismail et al, 2013;Karunakaran et al, 2018;Liew et al, 2019;Memon et al, 2011Memon et al, , 2012Rahman et al, 2013;C. Ramanathan et al, 2012;C.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The first stage of synthesizing the 152 literatures is dividing them according to 2 classifications, literatures from the developed countries and literatures from developing countries as presented in Table 2 & 3. (Afzal et al, 2019;Anish et al, 2019;Bhangale, 2016;Chandramohan et al, 2012;Cindrela Devi & Ananthanarayanan, 2017;Ghumare et al, 2019;Kant, 2018;Muthu Venkata Sekar & Mahalakshmi, 2018;Pai et al, 2018;Raju et al, 2017;Shaktawat & Vadhera, 2017;Shanmuganathan & Baskar, 2015;Sharma et al, 2020;Sharma & Goyal, 2019;Shrivastava et al, 2019;Subramani & Sivakumar, 2018;Velumani & Nampoothiri, 2019;Venkateswaran & Murugasan, 2017;Wanjari & Dobariya, 2016) Malaysia 20 (Abdullah et al, 2018;Afzal et al, 2019;Akram et al, 2017;Asmi et al, 2013;Azis et al, 2013;Hameed Memon et al, 2014;Haslinda et al, 2018;Ismail et al, 2013;Karunakaran et al, 2018;Liew et al, 2019;Memon et al, 2011Memon et al, , 2012Rahman et al, 2013;C. Ramanathan et al, 2012;C.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Poor site management and supervision, lack of coordination and substandard contracts were also identified as the second, third and seventh main risk factors that impacts delay of a construction projects in India (Doloi et al, 2012). Shrivastava et al (2019) also categorised railway construction project risks in India as contractors risk, DS, safety and security-related risk, financial risk, nature-related risk, government approvals and site clearances risk, quality related risk, contractor's cash flow related risk and fundamental risk. They showed that lack of coordination among parties, improper construction methods and poor site management were among the factors that contribute maximum among all the factors in terms of impact on cost and time.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that developing a competency standard is a foundation for the development of a training module that satisfies the competency gap in construction projects. Shrivastava, Gupta, Mittal, and Saxena (2019) identified and analyzed 84 risk attributes for project cost overruns using exploratory factor data analysis (EFA) of questionnaire surveys. The results identified the significance of construction workplace safety risks as the fifth highest contributor to project cost overruns.…”
Section: Cost Implications Of Safety Risk Incidents In Construction P...mentioning
confidence: 99%